2008
DOI: 10.1183/09031936.00066807
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and cerebrovascular abnormalities in mild COPD are worsened by chronic smoking

Abstract: Patients with chronic obstructive pulmonary disease (COPD) may develop hypercapnia and hypoxia, two main determinants of cerebral blood flow. The current authors tested whether cerebrovascular regulation was altered in mild COPD, modified by manoeuvres acutely improving autonomic cardiovascular modulation or influenced by smoking habit.In 15 eucapnic normoxic mild COPD patients (eight smokers) and 28 age-matched controls (14 smokers), midcerebral artery blood flow velocity (MCFV), end-tidal carbon dioxide tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 41 publications
2
50
0
1
Order By: Relevance
“…In young adults, cerebrovascular deficiencies are only observed following acute smoking (after smoking for 1 min) [23]. Similarly, in a healthy older population, smoking status was not a significant factor in determining the sensitivity to hypercapnia [7]. Interestingly, in this same study, BERNARDI et al [7] found that individuals who were current smokers had mild COPD and significantly lower cerebrovascular sensitivity to hypercapnia compared with individuals who only had mild airflow obstruction, without a smoking history.…”
Section: Physiological Response To Hypercapniamentioning
confidence: 75%
See 3 more Smart Citations
“…In young adults, cerebrovascular deficiencies are only observed following acute smoking (after smoking for 1 min) [23]. Similarly, in a healthy older population, smoking status was not a significant factor in determining the sensitivity to hypercapnia [7]. Interestingly, in this same study, BERNARDI et al [7] found that individuals who were current smokers had mild COPD and significantly lower cerebrovascular sensitivity to hypercapnia compared with individuals who only had mild airflow obstruction, without a smoking history.…”
Section: Physiological Response To Hypercapniamentioning
confidence: 75%
“…?mmHg -1 from a previously published study [7], we determined that to detect a significant difference in the cerebrovacular sensitivity to hypercapnia, each group would have to consist of 11 participants (using an unpaired two-tailed t-test and setting a at 0.05 and b at 0.80).…”
Section: Data and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced serum levels of Immunoglobulin G (IgG), an important anti-microbial antibody, have been detected in smokers when compared to non-smokers [96,97]. T-cell proliferative responses have also shown to be suppressed in smokers.…”
Section: Tobacco Smoke and Infectious Diseasesmentioning
confidence: 99%